Building national cyber resilience and protecting critical information infrastructure*. Issue 1 (2nd January 2016) - Tiirmaa-Klaar, Heli
ABSTRACT: The digital transformation poses a challenge to all societies and economies, with Information and Communication Technologies forming a substrate for critical services and economic growth. National cyber policy-makers are faced with many priorities, including protecting critical infrastructure, reducing cybercrime, raising awareness, and following national security and foreign policy interests. The protection of critical services and infrastructure, fight against cybercrime, cyber incident response and recovery form a basis of nations' cyber resilience in the digital era. In the light of recent cyber security regulations passed in the US and the European Union, the article offers an overview of how to organise and provide leadership for an efficient national cyber effort. It also discusses several methods from a public policy perspective of how to provide better cyber security for critical services and infrastructures.